Management strategies for the efficient energy production of brackish water desalination to ensure reliability, cost reduction, and sustainability - A. Bdour; A. Hejab; L. Almakhadmeh; M. Hawa (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Energy efficiency plays a crucial role in the success and sustainability of desalination technologies. Energy considerations are intricately linked with every aspect of planning, management, and operation in water desalination. This study aims to evaluate and enhance energy requirements, energy efficiency, and the economic feasibility of the Hashemite University photovoltaic brackish water reverse osmosis desalination plant at Hashemite University.METHODS: This study’s aims were achieved by conducting an energy audit and detailed assessment to identify the energy efficiency considerations that should be integrated into the facility’s planning, management, and operation strategies. To ensure accurate and reliable data collection and enable a comprehensive analysis of the plant’s energy performance, portable energy analyzers and loggers were employed to measure energy consumption, and measurements and verification techniques were recommended and implemented to establish the required baseline. A regression model was utilized to determine the potential energy savings resulting from energy conservation measures. This involved determining the expected savings by calculating the area between two curves: the new actual consumption of the brackish water reverse osmosis plant after implementing energy conservation measures and the curve generated by the model representing the usual consumption in the absence of energy conservation measures.FINDINGS: This study underscores the challenges faced by desalination, particularly regarding intensive energy consumption. It also presents innovative ways to achieve sustainability by emphasizing energy efficiency, integrating renewable energy, and advocating for a holistic water management approach. It was determined that the maximum specific energy consumption of the Hashemite University photovoltaic brackish water reverse osmosis plant was 0.625 kilowatts per cubic meter. This reflects the actual consumption and energy performance of the plant, which was found to be 192 percent more efficient than the estimated specific energy and 144 percent more efficient than the calculated specific energy. No energy conservation measures were implemented at this stage, as the plant was already operating efficiently. The measured data shall be considered as a baseline for future investigations and monitoring and evaluation of the plant. Many challenges were identified during the current work, including the low quality of raw water and minimal demand for freshwater, which resulted in lower operation hours outside of sun peak hours, while the direct utilization of photovoltaic energy is recommended.CONCLUSION: Renewable energy and energy recovery were recognized as potential sources for energy savings to achieve sustainable and long-term feasible operation and cost recovery at the Hashemite University photovoltaic brackish water reverse osmosis plant. The feasibility of the plant showed a fast payback period of up to 1.1 years. Utilizing clean solar photovoltaic energy to power the brackish water reverse osmosis plant led to a considerable reduction of greenhouse gases (mainly carbon dioxide). The estimated amount of carbon dioxide reduction during the project’s lifetime was 1,289,600 kilograms. The integration of solar energy showed promise for further enhancing energy efficiency and sustainability. This study contributes to making the desalination sector more environmentally friendly and economically viable, which is of paramount importance in addressing global water scarcity concerns.